2012
DOI: 10.1002/aur.1225
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, Coping Strategies, and Unmet Needs of Families with a Child with Autism Spectrum Disorder in Goa, India

Abstract: Autism Spectrum Disorders (ASD) are increasingly recognized in developing countries like India. However, little is known about the experiences of parents raising a child with ASD. This study aimed to describe the experiences of families in Goa, India with a view to understanding the unmet needs of families raising a child with ASD. Twenty in-depth interviews and nine focus group discussions were carried out with families of children with ASD and key community stakeholders such as special educators, teachers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 40 publications
14
141
1
4
Order By: Relevance
“…For example, in a recent UK qualitative study on experiences within the pre-diagnostic period, parents of children with autism reported that they were told that "there was nothing to worry about and their children would grow out of it" [16, p 380]. One father, who spoke about the long journeys and financial burden of multiple consultations in India, shared that he was given sleeping tablets for his child, because professionals thought that his child's autism would improve if he slept better [2]. This raises the additional issue of the extent to which health care professionals appropriately include families in the screening process to ensure improved uptake of recommendations for diagnosis and treatment [17].…”
Section: Early Identification Of Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent UK qualitative study on experiences within the pre-diagnostic period, parents of children with autism reported that they were told that "there was nothing to worry about and their children would grow out of it" [16, p 380]. One father, who spoke about the long journeys and financial burden of multiple consultations in India, shared that he was given sleeping tablets for his child, because professionals thought that his child's autism would improve if he slept better [2]. This raises the additional issue of the extent to which health care professionals appropriately include families in the screening process to ensure improved uptake of recommendations for diagnosis and treatment [17].…”
Section: Early Identification Of Asdmentioning
confidence: 99%
“…While some affected by the condition lead independent and fulfilling lives, others suffer serious disabling consequences as a result of having autism [35,37]. It is possible that, at least in some cases, secondary disabilities may emerge as a result of inadequate care, stigma, and isolation that those affected may experience, both in LMICs (e.g., [2,38,39]) and HICs (e.g., [3•, 40]). …”
Section: Emergence Of Disability and Its Impactmentioning
confidence: 99%
“…55 Divan et al (2012) discussed that, Autism Spectrum Disorders (ASD) are increasingly recognized in developing countries like India. However, little is known about the experiences of parents raising a child with ASD.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Social pressure, stigmatisation, and cultural influence, are common issues that have to be taken into account in developing countries. For example, in India, parents prefer to take their children to be evaluated using spiritual or alternative approaches, while in Saudi Arabia, China, and India, parents tend to delay meeting ASD practitioners in order to avoid the social stigma of having a child diagnosed with ASD (Divan et al, 2012, Seif Eldin et al, 2008, Sun et al, 2013a.…”
Section: Developing Countries and Asd Assessmentmentioning
confidence: 99%
“…In a study by Divan et al (2012), 10 parents of children with ASD who lived in a small city at Goa, Western India, were interviewed in order to understand their challenges and needs. Besides the parents, the study also interviewed 4…”
Section: Developing Countries and Asd Assessmentmentioning
confidence: 99%